2020
DOI: 10.3390/app10010339
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Uptake by Cement-Based Materials: A Spanish Case Study

Abstract: The European parliament has declared a global “climate and environmental emergency” on 28 November 2019. Given that, climate change is a clear strategic issue all around the world. Then, greenhouse gas emissions are reported by each country to the United Nations Framework Convention on Climate Change (UNFCCC) every year. In addition, The Intergovernmental Panel on Climate Change (IPCC) in the “2006 IPCC Guidelines for National Greenhouse Gas Inventories” give the procedure to calculate and manage the national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 21 publications
1
72
1
Order By: Relevance
“…In addition, the growth path of carbon dioxide uptake is represented by a growing curve for each considered application (civil engineering, building and mortars). As expected, the higher the surface/volume (S/V) ratio and carbonation coefficient (k co2 ), the higher the carbon dioxide uptake [23]. Figure 11.…”
Section: Co2 Uptake Of Concretes Manufactured With Portuguese Cementssupporting
confidence: 56%
“…In addition, the growth path of carbon dioxide uptake is represented by a growing curve for each considered application (civil engineering, building and mortars). As expected, the higher the surface/volume (S/V) ratio and carbonation coefficient (k co2 ), the higher the carbon dioxide uptake [23]. Figure 11.…”
Section: Co2 Uptake Of Concretes Manufactured With Portuguese Cementssupporting
confidence: 56%
“…It should be highlighted that noise and pollutant emissions are, again, indicators independent from the materials selected in the structure. However, recent studies have shown that cement-based materials can absorb CO2 during their lifecycle [12,50], 51]. In particular, during its lifecycle concrete can absorb 20% of the CO2 produced by calcination to manufacture the cement [12].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have shown that cement-based materials can absorb CO2 during their lifecycle [12,50], 51]. In particular, during its lifecycle concrete can absorb 20% of the CO2 produced by calcination to manufacture the cement [12]. Therefore, the buried M-30 solution will have a greater CO2 uptake compared with the non-buried solution, as the volume of concrete used to build the structure is bigger.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations